PERBANDINGAN PENGETAHUAN DAN SIKAP ANTARA REMAJA PUTRA DAN REMAJA PUTRI TENTANG TINDAKAN PENCEGAHAN HIV/AIDS - Lybella Meyrisa Sofni; Yulia Irvani Dewi; Riri ' Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this research to compare the knowledge and attitude level between teenage boys and girls about the prevention of HIV/AIDS. This research is a descriptive comparative study. The sampling technique of this research was stratified random sampling with 86 respondent that was selected based on inclusion criteria. This research used questionnaire for the variable knowledge, attitude and action. The univariate analysis was conducted and the result showed that teenage boys (37.2%) and girls (40.7%) had same level of knowledge about HIV/AIDS preventing behavior. Teenage girl have more possitive attitude (32.6%) than teenage boys (10.95%), teenage girls also more active (31.4%) than boys (16.3%) on HIV/AIDS preventing behavior. The result shows that there is had difference about attitude (p = 0.001) and action (p = 0.010) but no difference between boys and girls for the level of knowledge (p = 0.603) on HIV/AIDS preventing behavior. Recommendation for the school to increased health promotion about HIV/AIDS for the teenegers especially for the boys. Keywords: HIV/AIDS, teenage boys, teenage girl, behavior